Pola Komunikasi dalam Pelayanan Bimbingan dan Konseling di SDN 172 Enrekang - Ismaya Ismaya; Andi Ahmad Chabir Galib; Syawal Sitonda; M Yunus Sudirman; Mawaddatul Maykam (Universitas Muhammadiyah Enrekang, 2023)
This paper is the result of a descriptive qualitative research that aims to determine effective communication patterns in the implementation of guidance and counseling at Public Elementary School Number 172 Enrekang. The results showed that SD Negeri No. 172 Enrekang had 248 students, and did not yet have a teacher who specifically handles guidance and counseling, so that each class teacher became the executor of guidance and counseling services in his class. Class teachers who act as counselors provide guidance and counseling services to students through instilling values ​​in appropriate subjects, building empathetic communication, setting an example and giving appreciation and reinforcement. Public Elementary School Number 172 Enrekang should have a counselor who specifically handles guidance and counseling, given the large number of students, besides that counselors need to have special abilities, especially in terms of communicating with children, so that the guidance and counseling process can run better and more effectively.